2016
DOI: 10.4238/gmr.15027768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclusion or non-inclusion of short lactations and cow and/or dam genetic group on genetic evaluation of Girolando dairy cattle

Abstract: ABSTRACT. The objective of this study was to evaluate the effects of inclusion or non-inclusion of short lactations and cow (CGG) and/or dam (DGG) genetic group on the genetic evaluation of 305-day milk yield (MY305), age at first calving (AFC), and first calving interval (FCI) of Girolando cows. Covariance components were estimated by the restricted maximum likelihood method in an animal model of single trait analyses. The heritability estimates for MY305, AFC, and FCI ranged from 0.23 to 0.29, 0.40 to 0.44, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Among Sahiwal cattle, only 32.48% of total lactation records fell in the range of 251-350 days of lactation length, while more than three-fourth (76%) of total observations failed to reach the standard level of 305 milking days (Narwaria et al 2015). Vaccaro et al (1999) and Canaza -Cayo et al (2016) reported fewer incidences of short lactations upto 100 days as 3.8-4% and 2.5%, respectively whereas Facó et al (2009) reported a higher incidence of shorter than 120 days as 13.6% of lactations among dairy cattle.…”
Section: Introductionmentioning
confidence: 97%
“…Among Sahiwal cattle, only 32.48% of total lactation records fell in the range of 251-350 days of lactation length, while more than three-fourth (76%) of total observations failed to reach the standard level of 305 milking days (Narwaria et al 2015). Vaccaro et al (1999) and Canaza -Cayo et al (2016) reported fewer incidences of short lactations upto 100 days as 3.8-4% and 2.5%, respectively whereas Facó et al (2009) reported a higher incidence of shorter than 120 days as 13.6% of lactations among dairy cattle.…”
Section: Introductionmentioning
confidence: 97%